2015
DOI: 10.1083/jcb.201504035
|View full text |Cite
|
Sign up to set email alerts
|

Lamin A/C sustains PcG protein architecture, maintaining transcriptional repression at target genes

Abstract: Reduction of lamin A/C, which is evolutionarily required for the modulation of Polycomb group (PcG) protein–dependent transcriptional repression by sustaining PcG protein nuclear architecture, leads to PcG protein diffusion and to muscle differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 67 publications
7
104
0
Order By: Relevance
“…A recent study has also shown that lamin A/C play a role in the compartmentalization and function of the Polycomb group (PcG) of proteins, key regulators of development and differentiation (Cesarini, Mozzetta et al 2015). Depletion of A-type lamins leads to dispersion of PcG proteins, hindering their gene repressive functions.…”
Section: Molecular Mechanisms Behind Cellular Decline In Hgpsmentioning
confidence: 99%
“…A recent study has also shown that lamin A/C play a role in the compartmentalization and function of the Polycomb group (PcG) of proteins, key regulators of development and differentiation (Cesarini, Mozzetta et al 2015). Depletion of A-type lamins leads to dispersion of PcG proteins, hindering their gene repressive functions.…”
Section: Molecular Mechanisms Behind Cellular Decline In Hgpsmentioning
confidence: 99%
“…We used an in situ proximity ligation assay (PLA), which is based on the proximity of two antibody-binding events and can detect interactions for a distance of up to 40 nm. As chromatin fibers are expected to be between 10 nm and 30 nm in size, PLA is useful and has previously been used for the study of interactions between histone modifications and nucleosolic lamins (Cesarini et al, 2015). As shown in Fig.…”
Section: Macroh2a Is Required For the Attachment Of Repeats To Lamin B1mentioning
confidence: 99%
“…In the nucleoplasm, lamin A/C further interacts with the surface of polycomb-marked heterochromatin foci (Cesarini et al, 2015). In addition to the nuclear lamina, the nucleolus is the other nuclear structure with a major influence in genome organization and is surrounded by a shell of constitutive heterochromatin (Németh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in the nuclear space, PcG proteins are organized into aggregates called PcG bodies, mediated by intrinsic and extrinsic protein-protein interactions [ 1 ] whose assembly mirrors the chromatin architecture of PcG clustered targets. Interestingly, recent fi ndings have shown that PcG proteins are also able to crosstalk with the nuclear components [ 5 ], suggesting that the positioning of PcG bodies in the nucleus could be highly regulated.…”
Section: Investigating the Polycomb Group Of Proteins: Technologies àmentioning
confidence: 99%